Neurexin Superfamily Cell Membrane Receptor Contactin‐Associated Protein Like‐4 (Cntnap4) Is Involved in Neural EGFL‐Like 1 (Nell‐1)‐Responsive Osteogenesis. (29th June 2018) - Li, Chenshuang; Zheng, Zhong; Ha, Pin; Chen, Xiaoyan; Jiang, Wenlu; Sun, Shan; Chen, Feng; Asatrian, Greg; Berthiaume, Emily A; Kim, Jong Kil; Chen, Eric C; Pang, Shen; et al.
ABSTRACT: Contactin‐associated protein‐like 4 (Cntnap4) is a member of the neurexin superfamily of transmembrane molecules that have critical functions in neuronal cell communication. Cntnap4 knockout mice display decreased presynaptic gamma‐aminobutyric acid (GABA) and increased dopamine release that is associated with severe, highly penetrant, repetitive, and perseverative movements commonly found in human autism spectrum disorder patients. However, no known function of Cntnap4 has been revealed besides the nervous system. Meanwhile, secretory protein neural EGFL‐like 1 (Nell‐1) is known to exert potent osteogenic effects in multiple small and large animal models without the off‐target effects commonly found with bone morphogenetic protein 2. In this study, while searching for a Nell‐1‐specific cell surface receptor during osteogenesis, we identified and validated a ligand/receptor‐like interaction between Nell‐1 and Cntnap4 by demonstrating: 1) Nell‐1 and Cntnap4 colocalization on the surface of osteogenic‐committed cells; 2) high‐affinity interaction between Nell‐1 and Cntnap4; 3) abrogation of Nell‐1‐responsive Wnt and MAPK signaling transduction, as well as osteogenic effects, via Cntnap4 knockdown; and 4) replication of calvarial cleidocranial dysplasias‐like defects observed in Nell‐1 ‐deficient mice in Wnt1‐Cre ‐mediated Cntnap4‐ knockout transgenic mice. In aggregate, these findings indicate that Cntnap4 plays a critical role in Nell‐1‐responsive osteogenesis. Further, this is the first functional annotation for Cntnap4 in the musculoskeletal system. Intriguingly, Nell‐1 and Cntnap4 also colocalize on the surface of human hippocampal interneurons, implicating Nell‐1 as a potential novel ligand for Cntnap4 in the nervous system. This unexpected characterization of the ligand/receptor‐like interaction between Nell‐1 and Cntnap4 indicates a novel biological functional axis for Nell‐1 and Cntnap4 in osteogenesis and, potentially, in neural development and function. © 2018 American Society for Bone and Mineral Research.